Intention to maintain and willingness to stop: Applying a dual‐process model to understanding the maintenance of COVID‐19 preventive behaviors. Issue 1 (12th June 2022) - He, Mu; Chen, Juliet Honglei; Wu, Anise M. S.; Tong, Kwok Kit
Abstract: Preventive behaviors have played an essential role in coping with COVID‐19 and may continue to exerting a crucial impact on pandemic control in the future. This study aimed to evaluate the effectiveness of social‐cognitive factors on maintenance of COVID‐19 preventive behaviors based on a dual‐process model, which encompasses a reasoned path via the intention to maintain and a social reaction path via the willingness to stop. We collected a probability sample of 472 community‐dwelling adults. Social‐cognitive factors, behavioral tendencies, and preventive behaviors of COVID‐19 were measured. The results supported that the dual‐process framework could account for individual differences in preventive behaviors. Self‐efficacy and response cost significantly explained the intention to maintain preventive behaviors, while favorability of risk image and subjective norm significantly explained the willingness to stop preventive behaviors. Our findings proposed strategies for promoting individuals' maintenance of preventive behaviors during a pandemic. The development of prevention policies may focus on two paths: strengthening the intended path by enhancing self‐efficacy and decreasing response cost of preventive behaviors and monitoring and improving social influences, such as risk prototype and subjective norm, which can reduce the willingness to stop preventive behaviors.